MANAJEMEN PERSEDIAAN BAHAN BAKU UBI CILEMBU PADA INDUSTRI RUMAH TANGGA ANEKA OLAHAN UBI CILEMBU KHAS MA UTIK SUMEDANG JAWA BARAT - Raden Maulidya Khairunnisa; Pandi Pardian; Ernah Ernah; Mahra Arari Heryanto (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Aneka Olahan Ubi Cilembu Khas Ma Utik is a home industry that processes Cilembu sweet potatoes into food products, namely sweet potato chips. This home industry has not used the optimal inventory management method for purchasing raw materials so the supply of raw materials for producing sweet potato chips is lacking. This problem needs to control inventory to get optimal inventory of raw materials. The purpose of this study was to analyze the inventory of raw materials according to the Home Industry and the inventory of raw materials according to the EOQ method and the comparison of the raw material inventory system of the Home Industry with the Economic Order Quantity Method. This study uses a qualitative descriptive research design with case study techniques. The results showed that this home industry made purchases of raw materials for cilembu sweet potato as much as 11,760 kg/year with a purchase frequency of 12 times, the total inventory cost incurred was Rp. 7,980,000. Safety stock is not carried out due to shortage of raw materials. The reorder point is made when 150 kg of raw material remains, while according to the Economic Order Quantity (EOQ) method, the optimal purchase of raw materials reaches 15,777.78 kg/year with a frequency of 12 times per a year. The total cost of inventory incurred is Rp. 5,634,839.9/year. Raw materials that need to be reserved are 116.7 kg/month. The reorder point is carried out when the remaining raw materials are 279.7 kg / month, therefore the Economic Order Quantity (EOQ) method can reduce the cost of inventory incurred and determine the optimal amount of raw material purchases.